2022
DOI: 10.3389/fcimb.2022.935927
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram for clinical estimation of acute biliary pancreatitis risk among patients with symptomatic gallstones: A retrospective case-control study

Abstract: Background/PurposeCurrently, there are no effective tools to accurately assess acute biliary pancreatitis (ABP) risk in patients with gallstones. This study aimed to develop an ABP risk nomogram in patients with symptomatic gallstones.MethodsWe conducted a retrospective nested case-control study and data on 816 conservatively treated patients with symptomatic gallstones admitted to The First Affiliated Hospital of Harbin Medical University between January 6, 2007 and January 22, 2016 were retrospectively colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Previous studies have demonstrated that age is not only closely associated with the incidence of AP but also serves as an independent risk factor for AP mortality. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that age is not only closely associated with the incidence of AP but also serves as an independent risk factor for AP mortality. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Acute biliary pancreatitis (ABP) is the most common type of AP, accounting for approximately 40% of AP cases [ 6 ] and has a mortality rate ranging from 5% to 20% [ 7 ]. Risk factors for ABP include female gender, age over 70 years, and the presence of gallstones smaller than 5 mm [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The condition takes place when the bile acids to cholesterol ratio is disturbed to abnormal levels. [6][7] One of the most common primary bile acids are cholic acid and chenodeoxycholic acid that are called as the precursor of cholesterol. The primary bile acids undergo conversion into secondary and tertiary bile acids by the intestinal microbiota through hydroxylation and deconjugation.…”
Section: Introductionmentioning
confidence: 99%